Pengaruh Pendekatan Contextual Teaching And Learning Berbasis Inquiry Terhadap Keterampilan Proses Sains Siswa - Agus Puji Setya Ningsih (Universitas Muhammadiyah Sidoarjo, 2017)
The problem in this research is the less learning to train students' science process skills. This study aims to determine the positive influence of contextual teaching and learning approach based on inquiry to the skills of science process students of grade XI SMA Unggul N 4 Palembang. The research method used is quasi experimental design with design matching only pre-test post-test control group design. Population in this research is all class XI MIPA SMA Unggul N 4 Palembang. Sampling using purposiveive sampling technique to obtain class XI MIPA.5 as experiment class and XI MIPA.4 as control class. Technique of collecting data using test technique. The technique of analyzing test data using t-test technique. Based on the results of the test data analysis, the average value of post-test experimental class is 84.26, while the control class is 70.85. Hypothesis test results using t-test at a significant level of 5% obtained thitung> ttabel ie 6.77> 1.671. So it can be concluded that the contextual teaching and learning approach based on inquiry have a positive effect on students' science process skill.